2018
DOI: 10.1111/jgh.14361
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a concomitant elemental diet with maintenance anti‐tumor necrosis factor‐α antibody therapy in patients with Crohn's disease: A multicenter, prospective cohort study

Abstract: The addition of ED for Crohn's disease patients who responded to initial anti-TNF induction therapy was not found to improve outcomes. The efficacy of concomitant ED in other clinical settings, such as loss of response, needs to be clarified in the future (UMIN000009789).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 34 publications
(51 reference statements)
1
22
0
Order By: Relevance
“…Out of the 16 studies which compared clinical relapse rates between patients using MEN and those that did not, 9/16 (56%) of the studies demonstrated lower relapse rates in patients using MEN; 8/11 (73%) in adults [ 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ] and 1/5 (20%) in children [ 59 ]. Conversely, in 3/11 (27%) adult and 3/5 (60%) pediatric studies, clinical relapse rates did not differ between patients using MEN against those in the comparator group [ 31 , 60 , 61 , 62 , 63 , 64 ]. In one pediatric study, MEN use led to lower relapse rates only in patients not using any concomitant medication, with no significant differences observed in relapse rates between patients using MEN and azathioprine than those only using azathioprine [ 65 ].…”
Section: Literature Reviewmentioning
confidence: 95%
“…Out of the 16 studies which compared clinical relapse rates between patients using MEN and those that did not, 9/16 (56%) of the studies demonstrated lower relapse rates in patients using MEN; 8/11 (73%) in adults [ 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ] and 1/5 (20%) in children [ 59 ]. Conversely, in 3/11 (27%) adult and 3/5 (60%) pediatric studies, clinical relapse rates did not differ between patients using MEN against those in the comparator group [ 31 , 60 , 61 , 62 , 63 , 64 ]. In one pediatric study, MEN use led to lower relapse rates only in patients not using any concomitant medication, with no significant differences observed in relapse rates between patients using MEN and azathioprine than those only using azathioprine [ 65 ].…”
Section: Literature Reviewmentioning
confidence: 95%
“…EN does not directly induce an increase in anti-TNF-alpha antibody blood concentration or reduce antibody production. However, an increasing number of recent reports have shown how the use of EN in combination with an anti-TNF-alpha antibody is clinically useful due to the add-on effect of EN itself [40][41][42][43][44][45][51][52][53]. In the present review, in which these studies were meta-analyzed, the pooled OR for maintenance of remission or relapse with EN was 2.23 in the fixed effects model and 2.19 in the random effects model.…”
Section: Discussionmentioning
confidence: 53%
“…In retrospective studies, patients who were able to continue receiving EN for a prolonged period are analyzed as the EN group, enabling assessment of the effect of EN combination therapy; however, recruitment bias cannot be ruled out. According to the report by Hirai et al, although patient adherence was confirmed in the EN group prior to the enrollment in accordance with the protocol for the prospective cohort, only 29.7% were able to continue with EN at the targeted calorific content of 900 kcal over a 2-year period [45]. The authors considered that the low adherence in the EN group was the main reason why the efficacy of combination therapy with EN was not demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations